HUKUM ISLAM DAN TRANSFORMASI SOSIAL MASYARAKAT JAHILIYYAH - Hermawan, Sulhani (Jurnal Ilmiah Peuradeun, 2014)
Islamic law is holy commands of God that governs all aspects of the life of every Muslim, and includes legal materials is purely spiritual and religious materials. Islam came to the middle of Jahiliyyah society by bringing Shari'ah (legal sistem) is perfect so as to set a fair and egalitarian relations between human individuals in the community. Clearly, the Qur'an rejects the use of the law of Jahiliyyah which assessed full consideration lust and partiality towards certain groups in power in the society. Furthermore asserted that Islamic law is the only law that should be held down by humans because it comes from Allah and brings the principles of sosial justice and equality. Islamic law stands on the principles that should be maintained in absolute and universal. Those principles are the definitive teachings and the benchmark of understanding and acceptance of Islamic law as a whole. If then there are the rules of the Islamic law that seems incompatible with the egalitarian principles and other principles, then the rule must be read within the context of the surrounding social reality and pay attention to its function as a legal counter to the rules of law applicable non-egalitarian during Jahiliyyah.